Assessment of referrals to a district hospital maternity unit in South Africa - Mashishi, Mathiba Maria (My University, 2012)
Introduction: A functioning and effective referral system is essential to improve maternal care services. There are guidelines that identify the types of maternity care that should be provided at the different levels of care, and define referral pathways and appropriate management of patients at each level of care. Compliance with referral and patient management guidelines is important to ensure appropriate utilization of different levels of maternal care services, and to prevent maternal and peri-natal mortality. This study assesses the referral of pregnant women to Dilokong district hospital maternity unit for delivery, to evaluate the proportion of referred women who delivered at the appropriate level of care. Methods: This was a descriptive cross sectional study involving retrospective review of hospital records for mothers who delivered in the maternity unit of Dilokong hospital during January to December 2008. Data were collected from 400 records using a data extraction sheet. Data were collected on demographic variables, clinical and obstetric history, distance to Dilokong hospital, and type of referral (self-referred or health professional referred). Analysis determined the appropriateness of referrals for delivery at the Dilokong hospital level of care. Results: Most women delivering at the hospital maternity unit were self-referred and inappropriate for the level of care. A total of 333 women (85%) were self-referred and 57% were inappropriate for delivery at the hospital level of care. Most women used Dilokong hospital as their first contact with the health care system even though many lived closer to a clinic or CHC. Among self-referrals, only 121 (37%) were appropriate for delivery at the hospital level of care. The majority (74%) of health-professional referred women were appropriately referred for hospital delivery. The results also show that the majority (67%) and (53%) of self-referrals and inappropriate referrals respectively were brought to the hospital by ambulance. Conclusion: This study shows that referral pathways are not functioning in line with referral guidelines for maternal care. The bypass of primary care facilities by most women in the study results in inappropriate utilization and potentially overloading of the hospital maternity unit. Non-compliance with referral guidelines defies the efficient functioning of health services. This could be addressed by developing mechanisms to improve and continuously monitor compliance; and doing further studies to determine the contributory factors, particularly for self-referrals.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Public Health. Johannesburg, April 2012
Keywords: Referral and Consultation